Azure AI Engineer Associate (AI-102) Cert Prep: Implement Natural Language Processing Solutions. - O'Brien, Gerry (linkedin.com, 2024)
Prepare for the Implement Natural Language Processing Solutions domain of Microsoft Azure AI Engineer Associate (AI-102) certification exam.